The relationship between visceral adiposity index and estimated pulse wave velocity: insights from NHANES database - Liu, Yanwei; Yang, Shiqiang; Wei, Jun (Frontiers in Nutrition, 2025)
BackgroundObesity and arterial stiffness are known risk factors for cardiovascular disease, but the relationship between visceral adiposity index (VAI) and estimated pulse wave velocity (ePWV) is still unclear.MethodsThis study used cross-sectional study data from the National Health and Nutrition Examination Survey (NHANES) database from 2007 to 2016. After data cleaning, we performed a comprehensive weighted statistical analysis of the final dataset. This included data on demographics, medical history, test results, and chronic comorbidities. We used restricted cubic spline analysis to explore potential non-linear relationships between VAI and ePWV. We also performed weighted linear univariate and multivariate regression analyses to further explore the relationship between VAI and ePWV. Finally, we performed multiple subgroup analyses and interaction tests, as well as sensitivity analyses, to test the stability of this relationship.ResultsFinally, 10,458 adult participants aged 20 years or older were included in this study, with a mean (SD) age of 49.2 ± 17.4 years after weighted analysis. Restricted cubic spline analysis showed a potentially “inverted-L” non-linear relationship between VAI and ePWV (P for non-linearity: <0.001). The inflection point analysis suggests its inflection point is (1.48: 1.38–1.57). Linear multivariate regression analysis suggested a significant positive correlation between VAI (0.2SD) and ePWV values (β = 0.1, 95% CI 0.04–0.17, p < 0.001). The positive correlation between VAI (0.2SD) and ePWV levels remained stable in model analyses adjusted for all covariates. This association was also consistent across quartiles of VAI (p-value <0.001 for trend test). These findings remained stable and consistent in subsequent subgroup and sensitivity analyses.ConclusionIn this study, we found that elevated VAI values were significantly and positively associated with ePWV, especially below the inflection point of VAI less than 1.48. This association remained robust after adjustment for multiple confounders and was consistent across multiple subgroup analyses. This suggests that abdominal obesity may play an important role in atherosclerosis and highlights the importance of addressing abdominal obesity to reduce cardiovascular risk.